Analisis Faktor-Faktor yang Mempengaruhi Penyerapan Tenaga Kerja di Daerah Karesidenan Semarang - Alfaiz Biamrillah; Siti Fatimah Nurhayati (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2018)
Employment issues are a common and fundamental problem faced byall regions. These problems include low quality associated withproductivity, low wages and high unemployment rates that are notbalanced with the growth of the workforce. This study aims to analyzethe effect of population, inflation, gross regional domestic product(PDRB) and minimum wage of district / city (MSE) to the absorption oflabor in the residency area of Semarang. The analysis tool uses paneldata regression. The result of analysis shows that the best model usedis random effect model (REM). Gross Domestic Product (PDRB)variable and population have positive effect, while inflation and MSEhave no effect to the absorption of labor in Semarang residency area.